Ureaplasma Species Differentially Modulate Pro- and Anti-Inflammatory Cytokine Responses in Newborn and Adult Human Monocytes Pushing the State Toward Pro-Inflammation - Glaser, Kirsten; Silwedel, Christine; Fehrholz, Markus; Waaga-Gasser, Ana M.; Henrich, Birgit; Claus, Heike; Speer, Christian P. (Frontiers in Cellular and Infection Microbiology, 2017)
Background: Ureaplasma species have been associated with chorioamnionitis and preterm birth and have been implicated in the pathogenesis of neonatal short and long-term morbidity. However, being mostly commensal bacteria, controversy remains on the pro-inflammatory capacity of Ureaplasma. Discussions are ongoing on the incidence and impact of prenatal, perinatal and postnatal infection. The present study addressed the impact of Ureaplasma isolates on monocyte-driven inflammation. Methods: Cord blood monocytes of term neonates and adult monocytes, either native or LPS-primed, were cultured with Ureaplasma urealyticum (U. urealyticum) serovar 8 (Uu8) and U. parvum serovar 3 (Up3). Using RT-qPCR, cytokine flow cytometry and multi-analyte immunoassay, we assessed mRNA and protein expression of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-8, IL-12p40, IL-10 and IL-1 receptor antagonist (IL-1ra) as well as Toll-like receptor (TLR) 2 and TLR4. Results: Uu8 and Up3 induced mRNA expression and protein release of TNF-α, IL-1β and IL-8 in term neonatal and adult monocytes (p<0.01 and p<0.05). Intracellular protein expression of TNF-α, IL-1β and IL-8 in Ureaplasma-stimulated cells paralleled those results. Ureaplasma-induced cytokine levels did not significantly differ from LPS-mediated levels except for lower intracellular IL-1β in adult monocytes (Uu8: p<0.05). Remarkably, ureaplasmas did not induce IL-12p40 response and promoted lower amounts of anti-inflammatory IL-10 and IL-1ra than LPS, provoking a cytokine imbalance more in favor of pro-inflammation (IL-1β/IL-10, IL-8/IL-10 and IL-8/IL-1ra: p<0.01, versus LPS). In contrast to LPS, both isolates induced TLR2 mRNA in neonatal and adult cells (p<0.001 and p<0.05) and suppressed TLR4 mRNA in adult monocytes (p<0.05). Upon co-stimulation, Uu8 and Up3 inhibited LPS-induced intracellular IL-1β (p<0.001 and p<0.05) and IL-8 in adult monocytes (p<0.01), while LPS-induced neonatal cytokines were maintained or aggravated (p<0.05). Conclusion: Our data demonstrate a considerable pro-inflammatory capacity of Ureaplasma isolates in human monocytes. Stimulating pro-inflammatory cytokine responses while hardly inducing immunomodulatory and anti-inflammatory cytokines, ureaplasmas might push monocyte immune responses towards pro-inflammation. Inhibition of LPS-induced cytokines in adult monocytes in contrast to sustained inflammation in term neonatal monocytes indicates a differential modulation of host immune responses to a second stimulus. Modification of TLR2 and TLR4 expression may shape host susceptibility to inflammation.